2014
DOI: 10.1016/j.jad.2013.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal depression in Mexican American fathers: Demographic, cultural, and familial predictors

Abstract: Background Although maternal postpartum depression (PPD) is a well-documented phenomenon that has been the focus of a large body of literature, much less is known about the prevalence and predictors of depressive symptoms among fathers following the birth of a child. Particularly scarce is research with Mexican American men, an understudied population at high risk given limited socioeconomic resources and elevated rates of maternal PPD. Methods The current study used descriptive and path analyses to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 62 publications
2
41
0
3
Order By: Relevance
“…1,27 Roubinov ve ark.nın çalışmasında, ilk kez baba olan bireylerin %9'unda paternal depresyon görüldüğü saptanmıştır. 30 Benzer şekilde Condon ve ark.nın çalışmasında, ilk kez baba olan bireylerin stres düzeylerinin yüksek olduğu ve depresyon açısından risk altında oldukları belirlenmiştir. 31…”
Section: Sosyal Ri̇sk Faktörleri̇unclassified
See 1 more Smart Citation
“…1,27 Roubinov ve ark.nın çalışmasında, ilk kez baba olan bireylerin %9'unda paternal depresyon görüldüğü saptanmıştır. 30 Benzer şekilde Condon ve ark.nın çalışmasında, ilk kez baba olan bireylerin stres düzeylerinin yüksek olduğu ve depresyon açısından risk altında oldukları belirlenmiştir. 31…”
Section: Sosyal Ri̇sk Faktörleri̇unclassified
“…Yapılan çalışmalara bakıldığında, postpartum dönemde görülen depresyonun sadece anne değil baba için de bir risk olduğu görülmektedir. 5,12,18,[29][30][31] Bu nedenle postpartum sağlık hizmetleri planlanırken babanın da göz önüne alınması gerekmektedir. Postpartum döneme yönelik planlanan bu hizmetlerin sunumunda anahtar rol alan hemşirelerin, bu hizmetleri babalara da ulaştırması önemli bir ihtiyaç olarak karşımıza çıkmaktadır.…”
Section: Paternal Depresyon Ve Hemşi̇reni̇n Rolüunclassified
“…Correlates of postnatal depression in fathers include job quality (Giallo et al, ; Nishimura & Ohashi, ), unemployment (Roubinov, Luecken, Crnic, & Gonzales, ), lower education level (Ramchandani, Stein, et al, ), younger age (Bergström, ; Davé, Petersen, Sherr, & Nazareth, ), ethnic orientation (Roubinov et al, ), and social deprivation (Davé et al, ). Obstetric factors and child characteristics include unplanned pregnancy (Gao, Chan, & Mao, ; Koh, Chui, Tang, & Lee, ; Nishimura & Ohashi, ), the number of previous children (Ramchandani, Stein, et al, ), a female infant (Gao et al, ), and twins (Vilska et al, ).…”
Section: Correlates and Potential Consequences Of Paternal Depressionmentioning
confidence: 99%
“…There is a growing body of research on paternal postpartum depression that utilizes statistical analysis which has come to the similar conclusion that maternal postpartum depression is not a statistically significant predictor of paternal postpartum depression (Paulson et al 2016;Roubinov et al 2014;Top et al 2016) are not A more recent study that investigates the interaction of paternal and maternal postpartum depression through binary logistic regression, as I have employed, found that maternal depression does not predict paternal depression, but that for parents that both express depressive symptomology, mother's exposure to paternal postpartum depression did tend to worsen mother's depressive symptoms (Paulson et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…, in a 2014 study on postpartum depression in Mexican American fathers, researchers also found no correlation between maternal postpartum depression and paternal postpartum depression(Roubinov et al 2014). Roubinov et al's 2014 study had a sample of Mexican American fathers that were mostly lower income compared to Paulson et al's 2016 study which included mostly white middle-class individuals.…”
mentioning
confidence: 96%